Bactericidal activity of the fluoroquinolone DU-6859a alone and in combination with other antimicrobial agents against multiresistant enterococci - KORTEN, VOLKAN (My University, 1996)
The in vitro activity of DU-6859a (DU) alone and in combination with various antimicrobials was evaluated against multiresistant enterococci including some isolates with defined gyrA mutations. DU produced rapid in vitro killing against most enterococci that lacked resistance to ciprofloxacin, but it was not bactericidal against strains with MICs of ciprofloxacin of > or = 8 micrograms/ml, or against one of four strains with an MIC of ciprofloxacin of 4 micrograms/ml. The combination of DU with rifampin was antagonistic against two of two isolates tested. Combinations of DU and novobiocin, gentamicin, or a beta-lactam (amoxicillin, ampicillin-sulbactam, or amoxicillin-clavulanate) were generally indifferent. When different beta-lactams were used together, with or without DU, bactericidal activity was observed against some isolates. Despite the absence of synergistic interactions with other agents, DU is a promising fluoroquinolone for use against enterococci, although prior development of resistance to currently available fluoroquinolones diminishes some of its effect.
Keywords: Drug Combinations; Anti-Bacterial Agents; Microbial Sensitivity Tests; Gentamicins; Drug Synergism; Anti-Infective Agents; Ciprofloxacin; Drug Resistance, Microbial; Drug Antagonism; Genetic Variation; Antibiotics, Antitubercular; Rifampin; DNA Gyrase; DNA Topoisomerases, Type II; Drug Resistance, Multiple; Enterococcus; Fluoroquinolones; Lactams; Novobiocin; Quinolones